THE EUROPEAN UNION AND THE PARIS AGREEMENT - Miranda Natalie; Sherene Patricia; Erlyn Silveria; Ellya Dameria; Tiolas Sitanggang; Valerie Michelle (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
The Paris Agreement has undoubtedly impacted on other more personal environmental policies in each country worldwide. We are trying to explain the dynamics (changes and debates) that occur in the policy-making process by the actors and stakeholders in the Paris Agreement. For instance, with the Trump dismantling policy to leave the Paris Agreement that we called the free-riding strategy that affects not only the members within the Paris Agreement but also the environmental sector globally. We also contemplate the alternatives way to solve the environmental problem through the Paris Agreement, and a solution to the problem occurs within the members by considering the consequences under international law Keywords: Paris Agreement, Environmental Issue, European Union, President Trump